Influence of Auditor Switching, Public Accounting Firm’s Reputation, and Workload on The Audit Quality with The Audit Committee’s Effec tiveness as The Moderating Variable (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
Purpose: This research aims to examine the influence of auditor switching, KAP reputation, and workload on the audit quality with the effectiveness of the audit committee as a moderating variable.Method: This research uses the companies listed as LQ 45 on the IDX from 2016-2018. The data are processed using descriptive statistical and multiple linear analysis techniques with the absolute value difference test to examine the moderating variableFindings: The results show that auditor switching and KAP reputation positively influence audit quality, while the workload and effectiveness of the audit committee do not. The effectiveness of the audit committee does not moderate the influence of the independent variables on the audit quality.Novelty: This research is conducted from 2016 to 2018, where is a significant increase in stock offerings compared to the previous years. Furthermore, this research uses the effectiveness of the audit committee as a moderating variable